2021
DOI: 10.1016/j.bbamem.2021.183681
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different polymer belts on lipid properties in nanodiscs characterized by CW EPR spectroscopy

Abstract: With this study we aim at comparing the well-known lipid membrane model system of liposomes and polymer-encapsulated nanodiscs regarding their lipid properties. Using differential scanning calorimetry (DSC) and continuous wave electron paramagnetic resonance (CW EPR) spectroscopy, we characterize the temperature-dependent lipid behavior within 1,2-dimyristoyl-sn-glycero-3phosphocholine (DMPC) liposomes and nanodiscs made from such liposomes by application of various polymers based on styrene-co-maleic acid (SM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…EPR spectroscopy of spin-label doxyl moieties incorporated into the lipid bilayer in the 5th or 16th position combined with differential scanning calorimetry (DSC) allowed characterizing the temperature-dependent lipid properties in a DMPC model membrane surrounded by SMA, DIBMA, or poly(styrene-co-maleic amide sulfobetaine) (SMA-SB), as compared to liposomes [ 105 ]. The authors found that all three polymers broadened the main melting transition of DMPC, changed the water accessibility within the lipid bilayer, and imposed additional constraints onto the lipids.…”
Section: Formation Structure and Dynamics Of Lipodiscsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPR spectroscopy of spin-label doxyl moieties incorporated into the lipid bilayer in the 5th or 16th position combined with differential scanning calorimetry (DSC) allowed characterizing the temperature-dependent lipid properties in a DMPC model membrane surrounded by SMA, DIBMA, or poly(styrene-co-maleic amide sulfobetaine) (SMA-SB), as compared to liposomes [ 105 ]. The authors found that all three polymers broadened the main melting transition of DMPC, changed the water accessibility within the lipid bilayer, and imposed additional constraints onto the lipids.…”
Section: Formation Structure and Dynamics Of Lipodiscsmentioning
confidence: 99%
“…The copolymers exerted steric constraints onto the hydrophobic part of the lipids, while a small loosening effect was observable for the carbonyl-near membrane region [ 106 ]. The authors concluded that the choice of the solubilizing polymer is important in forming lipodiscs [ 105 ].…”
Section: Formation Structure and Dynamics Of Lipodiscsmentioning
confidence: 99%
“…The additional spectral component, featuring increased polarity and hydration in each model system, can be consistently explained with the addition of the amphiphilic polymers, i.e., SMA , and SMA-SB, , that change polarity directly plus disrupt the bilayer structure by providing the basis for increased water penetration into the core of the membrane. ,, On the other hand, increased restrictions of spin-label rotational mobility can either be the result of a polymer-induced formation of a condensed lipid phase , or by lipid–polymer interactions with the surrounding polymer itself. ,, To study this effect, we performed DSC measurements of SMALPs and SMA-SBLPs of both lipid compositions prior to the separation of the liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer stock solutions were prepared as previously described. , An appropriate amount of either SMA or SMA-SB was dissolved in saline tris buffer (50 mM tris, 300 mM NaCl, pH 7.4 in Millipore Milli-Q water with a specific resistance of ρ = 18.2 MΩ cm) to yield mass concentrations of 25 mg/mL (SMA) or 15 mg/mL (SMA-SB) at room temperature, followed by heating combined with ultrasonication for 30 min at 70 °C. After cooling down, both polymer stock solutions were stable for 2 weeks at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation